THE DIAGNOSTIC METHODS OF PLACENTA ACCRETA SPECTRUM DISORDERS - Alia Desmalia; Nuswil Bernolian; Abarham Martadiansyah; Theodorus Theodorus; Citra Dewi; Putri Mirani; Peby Maulina Lestari; Cindy Kesty (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Placenta Accreta Spectrum Disorder (PASD) is abnormal trophoblast invasion of part or all of the placenta into the myometrium of the uterine wall. Magnetic resonance imaging (MRI) examination is one of the tools that can help diagnosing PASD earlier, so that maternal morbidity and mortality can be reduced. This study aims to determine the prevalence, risk factors of PASD and the accuracy of Placenta Accreta Index Score (PAIS) and MRI, with histopathological examination in diagnosing PASD at dr. Mohammad Hoesin General Hospital (RSMH) Palembang during the 2018–2021. A descriptive study with a survey design on pregnant and intrapartum women with suspected PASD was performed at Department of Obstetrics and Gynecology at RSMH Palembang from 2018 until 2021. There were 72 study subjects who met the inclusion criteria. The relationship between the independent and dependent variables was analyzed using Chi Square and Fisher Exact. The cut-off point of the PAIS scores was analyzed using the Receiver Operating Curve (ROC). The comparison of the diagnostic value of PAIS and MRI scores used the Youden Index. Data was analyzed with SPPS version 22.0 From 72 subjects, 60 subjects (83.3%) were PASD and 12 subjects (16.7%) were not PASD. The risk factors of PASD in this study was surgical history more than once (PR = 4.600 (95% CI 1.261–16.781); p = 0.037). Youden Index values and PAIS accuracy were 0.782 and 0.953 while Youden Index values and MRI accuracy were 0.333 and 0.886. PAIS and MRI could be considered as diagnostic tools for PASD. However, overall, PAIS had a better diagnostic value than MRI.